Treands in atmospheric turbidity over India - SRIVASTAVA, H. N.; DATAR , S. V.; MUKHOPADHYAY, B. (MAUSAM, 1992)
Annual mean values of the turbidity coefficients at Indian Background Air Pollution Monitoring Network' (BAPMoN) were compared for the periods 1973-1980and 1981-1985. It was found that there is a general increase of turbidity during the latter period at all the stations except at Kodaikanal and Pune, suggesting the effect of anthropogenic sources of pollution. Short term influence of volcanic eruptions were also discernible from the observations at Kodaikanal. Spectral analysis (FFT) at these stations brought out the predominant modes which could be explained on the basis of climatology and aerosol dispersion characteristics. The long term atmospheric turbidity observations (1973-1985) presented in this paper provide reliable data set for assessing the aerosol impact on radiation climate.